Management of irritable bowel syndrome with constipation: a flexible approach to treating a complex condition with multiple symptoms. (July 2013) - Layer, Peter
Irritable bowel syndrome is a heterogeneous disease with a complex underlying pathophysiology and multiple symptoms – that is, clinical manifestation patterns. As such, management of irritable bowel syndrome requires a flexible approach tailored to the individual patient. This article reviews rational, evidence-based management strategy and treatment options for this variable condition.